Ionic Conductivity of Chitosan-Lithium Electrolyte in Biodegradable Battery Cell - Ali Benouar; Mohammed Reda Ahmed Bacha (Indonesian Journal of Chemistry, 2020)
The electrical conductivities of salts (LiCl, LiOH) in chitosan as an electrolyte in biodegradable batteries have been measured at the concentration range 10–100 mol m–3 in the temperature range 278–308 K. The data were interpreted in terms of ion–ion and ion–solvent interactions using the Fuoss paired ion. The fitting of Fuoss’ equation of 1978 to these data led us to an estimate of the ionic association by computing the conductimetric pairing constants. In order to optimize the use of the electrolyte in the clean lithium battery, the temperature dependency of conductivity will be studied using Arrhenius empirical equation. This equation was applied successfully in the temperature range used in this study.